2008
DOI: 10.1021/ja802317t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Stability of Monolayer-Protected Au38 Clusters

Abstract: A synthesis strategy to obtain monodisperse hexanethiolate-protected Au38 clusters based on their resistance to etching upon exposure to a hyperexcess of thiol is reported. The reduction time in the standard Brust-Schiffrin two-phase synthesis was optimized such that Au38 were the only clusters that were fully passivated by the thiol monolayer which leaves larger particles vulnerable to etching by excess thiol. The isolated Au38 was characterized by mass spectrometry, thermogravimetric analysis, optical spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
198
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(212 citation statements)
references
References 67 publications
14
198
0
Order By: Relevance
“…7,14,26,27 For comparison, a room temperature emission spectrum is plotted in the same figure (red line). The low-energy side of this emission band is at approximately the same energy as the absorption onset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,14,26,27 For comparison, a room temperature emission spectrum is plotted in the same figure (red line). The low-energy side of this emission band is at approximately the same energy as the absorption onset.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] The synthesis has reached the stage where clusters with a defined structural formula of Au(RS) can be routinely isolated. [6][7][8][9][10][11][12][13][14] These advances in synthesis and purification lead to the recent breakthrough in the crystal structure determination of the cluster. 15 It revealed that the monolayer is far from simple involving Au-thiolate oligomers that form a shell around the Au core in a "divide and protect motif".…”
Section: Introductionmentioning
confidence: 99%
“…These include Au 8 , [4] Au 18 , [5] Au 25 , [6] Au 38 , [7] and so on. Au 11 has also been the subject of recent research.…”
mentioning
confidence: 99%
“…For example, Au 15 , Au 18 , Au 25 [92], Au 38 [93] and Au 144 NCs [94] can all be prepared, and some of them have been fully characterized by single crystal X-ray diffraction [95]. These clusters break down the barriers between molecular systems and NP systems and are potential catalysts with unusual properties.…”
Section: Discussionmentioning
confidence: 99%